Nickel-assisted one-pot preparation of graphenic carbon matrices embedded with silicon nanoparticles as anode materials for lithium ion batteries. (July 2021) - Song, Changsheng; Zhao, Baoxun; Chen, Siyu; Ma, Jinyang; Du, Hongbin
Abstract: The unbearable volume expansion of silicon hinders its application for lithium-ion batteries (LIBs). The utilization of carbon coating to silicon has significantly improved its performance. However, the carbon coatings prepared via traditional methods are often too fragile to prevent the carbon-silicon electrode from pulverization during the long-term cycling process. Herein, a new, convenient, low-cost method is developed to prepare silicon-nickel-carbon composites with high mechanical strength and ion diffusivity for LIBs. Graphenic carbon network materials embedded with Si and Ni nanoparticles are prepared by using in-situ generated Ni 0 as catalysts to the thermal polymerization of polycyclic asphalt molecules. The composites show excellent LIB performance, superior to those prepared conventionally without the addition of nickel. The composite with 73.7 wt% Si shows an initial Coulombic efficiency of 87.5% and a charge capacity of 3191 mA h g −1 . The electrode expands only 16.5% in thickness after cycled 300 times at 2 A g −1 . Moreover, the composites with 19.6 wt% and 33.8 wt% Si exhibit capacities of 342 and 680 mA h g −1 after cycled 500 times at 2 A g −1, with capacity retention of 97% and 85%, respectively. The results show that the present method is promising for the preparation of stable silicon-carbon anode materials. Graphical abstract: Image 1